Аналіз методів розпізнавання образів та ідентифікації осіб за допомогою штучного інтелекту - Монахова, М. О. (ХНУРЕ, 2024)
At the moment, society is actively using Artificial Intelligence to facilitate certain actions, perform accurate and reliable calculations and, directly, identity recognition. This technology has found application in a variety of areas, including transportation, medicine, security, and business. For example, in airports and transportation the system of identity recognition is used to provide safe service and to control access. Banks and other facilities also use biometric technologies to verify their clients. However, with all its benefits comes questions about ethics and privacy of used data. In this paper we will not only argue the challenges of identity recognition but also build our own program using such programming language as Python.
Keywords: розпізнавання образів; ідентифікація осіб